The Impact of QRIS Digital Payments On Microenterprise Income In Palembang City - Muhammad Zulkarnain; Aurantia Marina; Nur Jumriantunnisah; Indri Ariyanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
One form of digital payment currently in use is the Quick Response Code Indonesian Standard (QRIS). Business actors—ranging from micro, small, to medium enterprises—have adopted this system due to its convenience for consumers in conducting payment transactions for purchased products. This ease of transaction can lead to increased sales and, ultimately, higher income for business owners. This study aims to examine the effect of QRIS-based digital payments on the income of microenterprises in Palembang City. The data utilized are primary data collected through questionnaires distributed to research respondents. A total of 100 microenterprise owners in Palembang were selected as the sample. The data analysis technique employed is simple linear regression.The findings indicate that QRIS digital payments have a significant positive impact on the income of microenterprises in Palembang City.